The Association Of Education Level And Knowledge To The Adherence To Meningococcal Meningitis Vaccination In Umrah Pilgrims At Kendari Port Health Office - Muhtar Muhtar; Narmi Narmi; Muhaimin Saranani (LPPM STIKes Karya Kesehatan, 2021)
Abstract Meningococcal meningitis is an acute disease of the lining of the brain caused by the bacterium Neisseria meningitides on the protective membrane that surrounds by the brain, spinal cord, which as a whole is called meninges. Meningococcal meningitis vaccination is given to people who will travel to meningitis endemic countries given at least 30 days before departure. The purpose of this research was to know the relationship between education level and knowledge with adherence to the meningitis vaccination for Umrah pilgrims at KKP Kendari. This study was an analytical descriptive using the cross-sectional study approach. The samples were 69 people. The sampling technique used a purposive sampling technique. The variables studied were adherence to meningitis vaccination, the level of education and knowledge. The analysis used chi-square test. The results showed that there was no association between education (ρ value = 0.360) and there was a relationship of knowledge (ρ value = 0.005) with adherence to the meningococcal meningitis vaccination at the KKP Kendari. The conclusion of this study is the level of education does not guarantee adherence to meningitis vaccination. It is recommended to increase counseling about the dangers of not vaccinating before the pilgrimage.